MoSe2 Nanoflowers for Highly Efficient Industrial Wastewater Treatment with Zero Discharge. Issue 23 (24th October 2021) - Lee, Jyun‐Ting; Mathur, Shaurya; Shen, Sophia; Wu, Jyh‐Ming; Chen, Jun
Abstract: Water pollution is one of the leading causes of death and disease worldwide, yet mitigating it remains a challenge. This paper presents an efficient new strategy for the processing of wastewater utilizing an accessible redox reaction with MoSe2 nanoflowers, which shows a strong oxidizing ability and permits the decomposition of dye molecules in dark environments without the need for an external power source. This reaction can treat wastewater at a decomposition rate above 0.077 min −1, even when interacting with organic pollutants at concentrations up to 1500 ppm. Theoretical calculations by Dmol 3 simulation elucidates that the reactions proceed spontaneously, and the kinetic constant ( k obs ) for this redox reaction with 10 ppm RhB dye is 0.53 min −1, which is 65 times faster than the titanium dioxide photocatalytic wastewater treatment. More importantly, the residual waste solution can be further utilized as a precursor to reconstruct the MoSe2 nanoflowers. To demonstrate the effectiveness and reusability, the treated effluent is directly used as the sole source of irrigated water for plants with no adverse effect. This method offers an eco‐friendly and more accessible way to treat industrial wastewater with zero‐discharge. Abstract : In this work, an efficient new strategy is presented for the processing of wastewater utilizing an accessible redox reaction with MoSe2 nanoflowers, which shows a strong oxidizing ability and permits the decomposition of dye molecules in dark environments without the need of an external power source.